MANAJEMEN OPERASIONAL DALAM PROSES PEMBELAJARAN METODE SENTRA - Rosita Rosita; Rica Nelvita; Nurul Hikmah Mawaddah (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
This qualitative research was conducted with a background enriching discourse and analyzing operational management in TK / RA Sentra, namely RA Daaruttuqo. In addition, researchers want to describe the theories and facts of operational management of education in the RA / TK Daaruttuqo School which almost fulfill the management function, but with a note that is an improvement in organizing due to an unprofessional and proportional position in the realm of teaching and educational staff (administration), but in The application of RA Daaruttuqo's child development theory has fulfilled the criteria for organizing, planning and managing the curriculum in the Early Childhood learning model very well namely the Sentra method. Because the age of kindergarten should be a time of imagination so that they can present their world with words, pictures and works through their world that is playing. This study uses a descriptive qualitative approach using Spradley analysis.Keywords: Education, Operational management, Early childhood, Qualitative, Sentra. ABSTRAKPenelitian kualitatif ini dilakukan dengan latar belakang memperkaya wacana dan menganalisa manajemen operasional di TK/RA Sentra, yaitu RA Daaruttuqo. Selain itu  peneliti ingin mendeskripsikan teori dan fakta manajemen operasional pendidikan di Sekolah RA/TK Daaruttuqo yang hampir memenuhi fungsi manajemen namun dengan catatan yaitu perbaikan dalam hal pengorganisasian dikarenakan ada posisi yang tidak professional dan proporsional dalam ranah tenaga pendidik dan kependidikan (administrasi), namun dalam aplikasi teori perkembangan anak RA Daaruttuqo telah memenuhi kriteria pengorganisasian, perencanaan dan pengelolaan kurikulum pada model pembelajaran Anak usia Dini dengan sangat baik yaitu metode sentra. Karena sepatutnya usia Taman Kanak Kanak adalah masa untuk berimajinasi sehingga mereka dapat mempresentasikan dunia mereka dengan kata-kata, gambar-gambar dan karya melalui dunia mereka yaitu bermain. Penelitian ini menggunakan pendekatan kualitatif deskrptif dengan menggunakan analisis Spradley.